Systemtherapie des Ovarialkarzinoms bei einem Rezidiv: Teil 1 : Leitthema - Marmé, Frederik (Die Onkologie, 2025)
Despite having received appropriate primary treatment, ovarian cancer, recurs in more than half of patients. In the past, recurrences were classified into “platinum-sensitive” and “platinum-resistant” on the basis of the platinum-free interval with a cut-off at 6 months and, depending on this, either treated again with platinum-based combination chemotherapy or platinum-free monochemotherapy. Today, however, this classification is primarily used to retrospectively compare data. The terms “platinum-sensitive” and “platinum-resistant” are still in use due to their simplicity and familiarity, but their meaning now goes far beyond an interval definition. For treatment decision-making, both disease- and patient-specific factors and preferences are also important. Predictive and prognostic factors such as BRCA status and homologous recombination deficiency (HRD) status must be taken into account when selecting treatment, e.g., postoperative residual tumor, which is the strongest prognostic factor, and the timing of surgery, i.e. whether it was primary surgery or after neoadjuvant chemotherapy. In collaboration with a specialized gynecological oncology surgery center, it is important to assess whether there is an indication for surgery for cancer recurrence.
Online publiziert: 18. Juli 2025
Gesehen am 11.09.2025